Communicative Awareness is the Key: Using The Rhetorical Triangle for Improving STEM Graduate Academic Writing - Rakedzon, Tzipora; Rabkin , Orit (Journal of Academic Writing, 2024)
The ability to carefully craft writing for an intended audience is crucial in creating persuasive rhetorical arguments. Learning to do so requires knowledge beyond IMRaD (Introduction, Methods, Results, Discussion). Many graduate students learn by mimicking this structure, yet lack audience awareness and overuse jargon, producing low-readability texts. What is more, they increasingly rely on AI-based writing tools that mimic the same structures that are already often poorly written. The results are too often uncommunicative articles that fail to persuade the intended audience. Therefore, we suggest writing pedagogy includes a deeper understanding of effective written science communication using the rhetorical triangle. As graduate students most readily understand the importance of logos, i.e., the scientific content, our job as writing instructors should be to emphasize the role a carefully aimed pathos and ethos plays in producing highly readable, persuasive, publishable articles. To this end, this paper first presents a brief background on the IMRaD structure before outlining the much-overlooked role of the rhetorical triangle in scientific writing. Specifically, we offer a detailed table for graduate students to use in science, technology, engineering and mathematics (STEM).